2008
DOI: 10.1002/col.20403
|View full text |Cite
|
Sign up to set email alerts
|

Interference colors of thin oxide layers on titanium

Abstract: This work deals with the characterization of the color properties of different titanium oxide films, obtained by means of anodic oxidation. The color of these oxides varies with film thickness, since it is due to light interference phenomena taking place at the metal-oxide-air interfaces. Color measurements were carried out by using spectrophotometry techniques: the values obtained belong to the colorimetric space CIELAB, which is defined as standard colorimetric space. The results of these analyses were relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 11 publications
8
82
0
10
Order By: Relevance
“…Figure 3 shows the colorations of the specimen surfaces after the anodizing procedures due to the interference effect. 27,28 Depending on the anodic voltages, the surface follows a chromatic scale and varies from golden to dark yellow violet color after anodizing at voltages between 10 V and 60 V in the sulfuric acid. For the phosphoric acid, dark golden to pale yellow color are displayed after anodizing from 10 V to 60 V. Figure 4 shows the scanning electron micrographs of the anodic films formed by anodizing at voltages from 10 V to 60 V in the sulfuric and phosphoric acids.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the colorations of the specimen surfaces after the anodizing procedures due to the interference effect. 27,28 Depending on the anodic voltages, the surface follows a chromatic scale and varies from golden to dark yellow violet color after anodizing at voltages between 10 V and 60 V in the sulfuric acid. For the phosphoric acid, dark golden to pale yellow color are displayed after anodizing from 10 V to 60 V. Figure 4 shows the scanning electron micrographs of the anodic films formed by anodizing at voltages from 10 V to 60 V in the sulfuric and phosphoric acids.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in color depends on the thickness, due to interference phenomena that occurs among the oxide, substrate and visible light [35,36]. [25] and Lee et al [26] reported the dependence of the layer's surface morphology on the electrolyte composition.…”
Section: Characterization Of Titanium Oxide Filmsmentioning
confidence: 99%
“…2c) at high voltage (90 V) for both untreated Ti foil 35,39 and polished substrate. For the latter, the higher quantity of energy required during anodizing (as proved by the higher currents circulated in the cell, Fig.…”
Section: Resultsmentioning
confidence: 99%